Verdade apócrifa e desinformação: estratégias de simulação e de ressignificação de sentidos em a A verdade dos Fatos - Chaise, Maria Joana Chiodelli (2022)
This research is entitled apocryphal “Truth” and disinformation: simulation strategies and resignification of meanings in “A Verdade dos Fatos” and develops an investigative path which general objective is to analyze the scenographies that are built from the narratives of a checking pseudo-agency, identifying the discursive ethos resulting from these discourses highlighted and disguised as checks, both as an individual representation, the image of itself, and as a collective construction based on the precepts of post-modern culture. The theoretical framework is based on the concepts of Dominique Maingueneau relating to scenography, ethos, detachability and simulacrum (2008b, 2008c, 2011, 2020). Furthermore, the study appropriates contributions from Traquina (2005), Bucci (2019a) and Charaudeau (2012) to discuss the journalistic production of truth and Bucci (2019b), Ferrari (2019) and Wardle (2020) aiming to understand disinformation, as well as D’Ancona (2018), Santaella (2019), Kakutani (2018) and Dunker (2017) in formulating the concept of post-truth. The research is classified as descriptive, bibliographic and documentary with a qualitative approach. The corpus that allows this study is a pseudo-agency entitled “A Verdade dos Fatos” which has a profile on the social media Twitter (https://twitter.com/v_dosfatos). The research corpus consists of a sample of three Twitter publications, which cite checking agencies or communication vehicles. Terms like 'left-checking', 'extreme press' and ‘fake news’ were chosen as markers of the corpus selection by indicative of an explicit ideological positioning and revealing of the hyperpartisan nature of the pseudoagency. From the research, we arrived at the following thesis: the scenography instituted in the circulation of statements generated by disinformation contents is established as a discursive strategy for economic and political gains. This dynamic is largely due to a process of disqualification of the traditional press, caused by the circulation of representations and simulacra disguised as fact checks. The results indicate that the “A Verdade dos Fatos” embodies, in the construction of scenographies, political-media discourses of circulation in the context of post-truth that simulates the verification and manipulation of information, which leads to the projection of a denialist, conservative, militant and imposter ethos, an anti-model of the agencies of professional check. Readers of the “A Verdade dos Fatos” inhabit this ethical world through the incorporation of a serious guarantor, a sense that has already been deposited in the memory of the discursive community, the social network being the counterpoint of traditional journalism.